Formulation, optimization and characterization of nanostructured lipid carrier of nitrofurantoin (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Nitrofurantoin is effective against many urinary tract pathogens. It acts as bacteriostatic and/or bactericidal by inhibiting DNA-RNA protein& cell wall synthesis. Nanostructured Lipid Carriers (NLCs) of NFT was prepared by Hot Homogenization Process. Glyceryl Monostearate and Miglyol 812 were heated at 80ºC temperature on hot plate. In the melted lipid, drug was added with continuous stirring at high speed homogenization. Formulation NLC12B has % Entrapment efficiency 89.1 ± 0.5, PDI 0.11 ± 0.01 and mean particle size 237 ± 7nm represents narrow particle size distribution. Spherical feature of NLCs with better uniformity without aggregation of Nitrofurantoin loaded NLC was confirmed by TEM. Moreover, efficient miscibility of drug in lipids was confirmed by the absence of intense and characteristic peak of NFT in XRPD. After 6 month storage at 2-8°C there was no significant changes in the PDI as well as mean particle size.